General method to synthesize aggregation‐induced emission molecules via carbon‐sulfur bond activation - Bowei Ma; Xinyu Liang; Gu Xu; Guanghao Zhang; Lutang Zhao; Liangzhuo Ma; Wenbin Xie; Xiang Li; Qinqin Shi; Kaikai Wen; Hui Huang (Aggregate)
Abstract Poly‐substituted olefins, one of the most important aggregation‐induced emission luminogens (AIEgens), have garnered significant attention due to their various applications in chemical‐ and bio‐sensing, bio‐imaging, and opto‐electronics. However, the synthetic methods for these olefins remain limited, impeding the progress of AIEgens. This study introduces an unprecedented cross‐coupling reaction between aryl sulfonium triflates and tosylhydrazones from naturally abundant thioethers and ketones. The generality of this method is exemplified by the facile synthesis of over forty poly‐substituted olefins. Importantly, the luminescent properties of these AIEgens (e.g., quantum yield and emission color) can be easily tuned by adjusting the substituents of the electrophile and nucleophile substrates, exhibiting excellent performance in bio‐imaging. Notably, the mechanistic studies reveal the critical role of β‐H elimination in the formation of the double bond. This contribution provides an efficient method to synthesize poly‐substituted olefins, pushing forward the development of AIEgens.